PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN COOPERATIVE LEARNING TEKNIK INDEX CARD MATCH DI KELAS IV - Marliana, Eva; Margiati, K Y; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem of research "Whether by using cooperative learning index card match techniques can improve student learning outcomes in learning the use of units of time in class IV Elementary School 11 Pontianak East?".Using descriptive method. The Class Action Research Form is collaborative. The subjects of the research are teachers as researchers and students of class IV which amounted to 24 people. Using direct observation techniques and documentation techniques, data collection tools of observation sheets and test instruments. Score data of teachers' ability to design and implement learning using cooperative learning index card match technique can improve learning outcomes of learners in learning class IV Mathematics. The study was conducted 3 cycles. Every cycle I meeting. The results achieved in this study the ability of teachers to design the learning cycle with an average score of 2.70, cycle II 3.36, cycle III 3.93. The ability of teachers to implement learning cycle I average 3.05, cycle II 3.53, cycle 3 3.81. Student learning outcomes in learning cycle I average 70.42, cycle II 82.29, cycle III 90.21. Implementation of cooperative learning index card match techniques in learning Mathematics can improve student learning outcomes fourth grade Elementary School 11 Pontianak East. Keywords:Learning Outcomes, Cooperative Learning Index Card Match Techniques, Mathematics.